Enhancing Inventory Accuracy in Manufacturing through the Implementation of Odoo Enterprise Resource Planning and Inventory Management Systems - Febryawan, Rizky; Hidayat, Yusup Rachmat (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
The phenomenon in this study originates from the discrepancy between actual stock and data recorded in the Enterprise Resource Planning Odoo system used by PT Paramita Bangun Sarana Tbk. This mismatch leads to decreased operational efficiency, distribution bottlenecks, and the risk of inaccurate decision-making. The purpose of this study is to examine the influence of Enterprise Resource Planning Odoo and Inventory Management on Inventory Accuracy Improvement at PT Paramita Bangun Sarana Tbk, Jakarta. This research employs a quantitative method with a descriptive approach. The population consists of employees from the purchasing, logistics, and warehouse divisions. The sample includes 45 respondents selected using a saturated sampling technique. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R ²). The results show that both partially and simultaneously, Enterprise Resource Planning Odoo and Inventory Management significantly influence Inventory Accuracy. This is evidenced by the F-test significance value of 0.000 < 0.05. The t-test results show a significance value of 0.000 for Enterprise Resource Planning Odoo and 0.006 for Inventory Management, both less than 0.05. These findings indicate that ERP Odoo and Inventory Management have a significant effect on Inventory Accuracy. The coefficient of determination (R ²) indicates that Enterprise Resource Planning Odoo and Inventory Management contribute 92.3% to the improvement of inventory accuracy at PT Paramita Bangun Sarana Tbk, while the remaining 7.7% is influenced by other variables not examined in this study.